Doxorubicin and sorafenib release from mesoporous silica nanoparticles coated with polydopamine – influence of mechanical and chemical stimuli on the process - Ostrowska, Sylwia; Szukowska, Monika; Kim, Shinik; Kim, Yeonho; Wawrzyniak, Dariusz; Mrówczyński, Radosław (Frontiers in Coatings, Dyes and Interface Engineering, 2025)
In this paper, we present results of a study on the influence of different experimental conditions on drug release, for the two anticancer drugs: doxorubicin (DOX) and sorafenib (SO), from mesoporous silica nanoparticles coated with polydopamine (PDA) shell. We tested the drugs release from the carrier into buffers of different pH (4.5; 5.5; 7.5) and with the addition of H2O2 or glutathione (GSH), while stirring the carriers in a flask or shaking them in a thermoblock, keeping the same time intervals, temperature and frequency. The obtained results and performed statistical analysis prove that the way the drug release tests are conducted has a significant influence on the efficiency of release of both drugs from the carrier. Thus, our results are of great importance for characterization of multimodal nanocarriers for biomedical application in terms of drug release and bring new knowledge for their methodological investigation.